Severity of Reactions in Double-Blind Placebo-Controlled Food Challenges: New Insights From the EuroPrevall Outpatient Clinic Study - Rosialzira N Vera-Berrios; Alejandro Gonzalo-Fernández; Barbara K Ballmer-Weber; Riccardo Asero; Laura Barreales; Simona Belohlavkova; Frédéric de Blay; Michael Clausen; Monika Jedrzejczak-Czechowicz; André C Knulst; Thuy-My Le; Nikolaos G Papadopoulos; et al. (Journal of Investigational Allergology and Clinical Immunology, 2026)
Background: Oral food challenge, particularly double-blind placebo-controlled food challenge (DBPCFC), is the gold standard for diagnosis of food allergy, although safety concerns limit its widespread use. Objectives: To evaluate the severity of reactions during DBPCFCs and to identify predictors of severe reactions. Methods: DBPCFCs from the EuroPrevall outpatient clinic study were analyzed in patients reporting immediate reactions to milk, egg, fish, shrimp, peanut, hazelnut, celeriac, apple, and/or peach. Patients with prior life-threatening anaphylaxis were excluded. Reaction severity (patient-reported and DBPCFC-elicited) was assessed using the Food Allergy Severity Score. A 2-step modeling strategy based on generalized estimating equations was applied to identify predictors of a positive DBPCFC, and, among positive challenges, predictors of anaphylaxis. Results: Among 514 DBPCFCs performed, 190 (36.9%) were negative, 30 (5.8%) uncertain, and 294 (57.2%) positive (102 mild oropharyngeal reactions [19.8%] and 192 systemic reactions [37.4%], of which 160 were moderate and 32 severe). The 32 severe reactions comprised 30 cases (30/514 [5.8%]) with lower respiratory involvement (16/30 with cough or dyspnea) and 2 anaphylaxis with hypotension (2/514 [0.4%]). DBPCFC reactions were less severe than patient-reported reactions (P0.35 kUA/L predicted positivity, whereas prior reaction severity and egg challenge were predictors of anaphylaxis. Conclusion: While systemic reactions during DBPCFCs were frequent, severe anaphylaxis was rare, supporting the safety profile of DBPCFCs when appropriately conducted. Key predictors of reactivity include atopic dermatitis and food-specific sensitization, while prior severity points to a risk of anaphylaxis. These findings may help risk stratification and patient selection in clinical practice.